Improvements in the thermal behaviour of date palm/bamboo fibres reinforced epoxy hybrid composites. (1st December 2021) - Jawaid, M.; Awad, Sameer; Fouad, H.; Asim, M.; Saba, N.; Dhakal, Hom N.
Abstract: Natural fibre–reinforced epoxy composites have been increasingly utilised in construction and building applications. These materials introduce cost-effective alternatives to conventional materials and their utilisation often has related to financial advantages that are immediate and can be expected over the structure service life. In this work, the results of thermal, dynamic-mechanical, and thermal-mechanical properties of date palm fibre (DPF)/bamboo fibre (BF) hybrid composite were compared to bamboo fibre-reinforced epoxy to demonstrate the importance of hybridization. The thermal stability was improved when DPF/BF fillers were added in epoxy resin comparatively to BF reinforced epoxy. The glass transition temperature (Tg ) was increased by incorporating the date palm fibre/bamboo hybrid composite in epoxy compared to the BF reinforced epoxy. The thermal expansion was enhanced by modifying the hybrid composites in epoxy in contrast to the single fibre composites, without hybridisation. Hence, the hybridisation technique of date palm fibre with bamboo has improved the thermal and thermal-mechanical properties suitable for several applications including non-structural applications.